Frequent attenders in primary health care: A concept analysis. (October 2018) - Kivelä, Kirsi; Elo, Satu; Kääriäinen, Maria
Abstract: Objectives: Frequent attendance is a well-known phenomenon in health care systems. A small proportion of patients make a high rate of visits to primary health care physicians. However, due to the diversity of this phenomenon, there is no generally accepted definition of the frequent attender. The aim of this analysis was to define the concept of the frequent attender in primary health care. Design: A concept analysis. Data sources: The literature was searched using electronic databases (MEDLINE, CINAHL, and Scopus) and a manual search was performed for studies published from 2000 to 2016. The inclusion criteria covered frequent attenders in primary health care examined by quantitative or qualitative studies published in English or Finnish. Review methods: Walker and Avant's (2010) strategy for concept analysis was used. Uses of the concept were studied, and attributes, antecedents, and consequences of the concepts were defined. Results: A total of 59 articles provided data for this concept analysis. Four defining attributes of frequent attenders were identified: the feelings of symptoms, perceived poor health status, lower quality of life and frequent visits to a primary health care provider. Antecedents included the patient's individual characteristics, the primary health care system, and the patient-physician relationship. Consequences were divided into two categories: those for frequent attenders and those for society. Consequences for frequent attenders included: follow-up investigations and visits, social disadvantages, and economic costs. Consequences for society included: the costs to the national economy and the consumption of health care resources. Conclusion: A theoretical definition and a conceptual model of the frequent attender were developed. The definition and the proposed empirical referents of all four attributes can be used to validate the presence of frequent attenders and to develop theory-based applications. Future research on frequent attenders is needed to develop and assess possible interventions.